Kompetisi Gulma Teki Terhadap Pertumbuhan Dan Produksi Bawang Varietas Super Philip Dan Varietas Bauji - Hasna Hasna; Zauzah Abdullatif; Sofyan Samad (Jurnal Pertanian Khairun, 2022)
ABSTRACTShallot is a primary commodity with high economic value. However, the productivity of shallot is still low due to the competition with nutgrass. Nutgrass reduces the productivity of shallot down to 50 - 80%. This study aimed to analyze the impact of nutgrass population towards the growth and productivity of shallot, particularly the Super Phillip and Bauji varieties. This study also aimed to find the most adaptable shallot variety in regards to the combination of nutgrass in Wayamiya Village of East Bacan District in South Halmahera Regency from January to March 2020. The methods used in this study were Randomized Complete Block Design (RCBD) in a factorial pattern consisting of two factors and Replacement Series Methods. The latter was used to analyze the interaction of these two plant species and the combination of both. The variables observed include the height of the plant (cm), the number of seedlings, the weight of fresh bulb (g), the air-dried weight (g), the dry weight without stover (g), the average diameter of air-dried bulb (cm), the fresh weight of nutgrass (g), the dried weight of nutgrass (g), and the numbers of nutgrass bulbs per cluster and plot. Based on the variance analysis calculations, the population of nutgrass had a real impact on produced shallots, particularly in terms of height (cm), weight of fresh bulb per plot, weight of dried bulb per plot, weight of dried bulb without stover, and diameter of bulb per plot. The relative yield total (RYT) and Relative Crowding Coefficient were used to examine the occurrence of competition between the two plants. The result of this study revealed the production of dried super phillip bulb without the presence of nutgrass was 9,5 tons/hectare. Meanwhile, with the presence of 4 nutgrass (T1), 8 nutgrass (T2), and 12 nutgrass (T3), the average weight of dried super phillip bulb was 6 tons/hectare. This showed a decrease of 3 tons/hectare or around 30%/hectare. Moreover, in regards to dried bauji bulb without the presence of nutgrass, the production was 9.3 tons/hectare. With the presence of 4 nutgrass (T1), 8 nutgrass (T2), and 12 nutgrass (T3), the dried bauji bulb production decreased to 3.3 tons/hectare or around 60%/hectare. There was a negative interaction between bauji shallots with 10% of nutgrass treatment in the planting. In this case, the RYT value was 1. The Relative Crowding Coefficient value of super phillip shallots with 10%, 20%, and 30% of nutgrass populations was more than one. This indicated the super phillip variety was adaptable with the presence of nutgrass. Meanwhile, the Relative Crowding Coefficient value of bauji shallots was below one.Keywords: : Nutgrass, Shallot, Competition